Pengaruh Kualitas Pelayanan terhadap Loyalitas Pelanggan Jasa Transportasi Online GOJEK di Kota Padang - Putra, Febrian Febrilium Tri; Nio, Suci Rahma (Al-DYAS, 2024)
Transportation is one of the most important parts of life today. With the development of the times, transportation can also be accessed online using an application called GOJEK. This research is a quantitative study that aims to see the effect of service quality on customer loyalty for gojek online transportation services in Padang city. Respondents in this study amounted to 108 people with purposive sampling technique. The data was analyzed using simple regression analysis. The results showed that there was no significant influence between service quality and customer loyalty for gojek online transportation services in Padang city.